Kesetaraan Gender dan Panggilan Perempuan dalam Pemberitaan Injil - Ardianto Lahagu; Fredy Simanjuntak; Uswatun Hasanah; Jabes Pasaribu (Jurnal Teologi Gracia Deo, 2024)
Even though the patriarchal cultural system is still inherent in Indonesia, especially in Christian society, which shows the dominant centrality of men in the Church and family, this research reveals the phenomenon of an increasing tendency for women to become more religious. In carrying out religious responsibilities, such as attendance at weekly services, daily prayer, witnessing, and preaching the Gospel in the family, women are exposed to gender disparities related to patriarchal traditions. This article aims to discover God's intended design for women as equal partners in preaching the Gospel by exploring women's responses to their call to preach the Gospel in the context of gender equality amidst men's function as priests in the family; preaching the Gospel is considered to continue. The author uses a qualitative approach through Phenomenological Studies. The research results highlight factors such as gender equality, which cannot be separated from the Bible, the reality of the rise of women as one of the church's strengths in ecclesiastical vocations, and gender responsibility as an essential element in designing women's roles in preaching the Gospel. AbstrakMeskipun sistem kebudayaan patriarki masih melekat di Indonesia, khususnya dalam masyarakat Kristen yang menunjukkan dominasi sentralitas laki-laki di Gereja dan keluarga, penelitian ini mengungkap fenomena peningkatan kecenderungan perempuan menjadi lebih religius. Dalam menjalankan tanggung jawab kewajiban religious (keagamaan), seperti kehadiran dalam pelayanan mingguan, doa harian, bersaksi, dan memberitakan Injil dalam keluarga, memperhadapkan perempuan pada kesenjangan gender yang terkait dengan tradisi patriarki. Artikel ini bertujuan untuk menemukan desain yang dimaksudkan Allah untuk perempuan sebagai mitra setara dalam pemberitaan Injil, dengan menggali respons kaum perempuan terhadap panggilan mereka dalam pemberitaan Injil dalam gugus kesetaraan gender ditengah fungsi laki-laki sebagai imam di keluarga, pemberitaan Injil dianggap tetap harus berlanjut. Penulis menggunakan pendekatan kualitatif melalui Studi Fenomenologi. Hasil penelitian menyoroti faktor-faktor seperti kesetaraan gender yang tidak dapat dipisahkan dalam pandangan Alkitab, realitas kebangkitan perempuan sebagai salah satu kekuatan gereja dalam panggilan gerejawi, dan tanggung jawab gender sebagai elemen penting dalam merancang peran perempuan dalam pemberitaan Injil.